The Role of Work Environment towards Entrepreneur Commitment on the Cooperative in Sidoarjo, Indonesia - Moch. Hidayatullah; Dewi Andriyani (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to determine the effect of the work environment, organizational culture, and work motivation on entrepreneurial commitment to SIDOARJO INTAKO COOPRATION. This research is a quantitative research with hypothesis testing. The sample used in this study were 60 employees at SIDOARJO INTAKO COOPRATION. The analytical tool used is multiple linear regression analysis, coefficient of determination (R2), partial correlation coefficient, t test, F test and classical assumption test using SPSS version 24.0 for windows. This primary data was obtained from a questionnaire whose measurement used a Likert scale that was tested for validity and reliability and the data was declared valid and reliable. The results of this study prove that the work environment, organizational culture, and work motivation simultaneously influence commitment entrepreneurs. work environment partially influences entrepreneur commitment, organizational culture partially influences entrepreneur commitment and work motivation partially influences entrepreneur commitment. In addition, organizational culture variables have the most significant influence on entrepreneurial commitment in SIDOARJO INTAKO COOPRATION.